Diskursus Nāsikh-Mansūkh dalam Perspektif Ulama Klasik dan Kontemporer - Hakim, Muhammad Haris Abdul; Rosidah, Aminatur (Canonia Religia, 2024)
The concept of nāsikh and mansūkh, which pertains to the abrogation and replacement of legal rulings in the Qur'an, has long been a subject of scholarly debate across generations. This terminology reflects the dynamic nature of Islamic legal discourse, wherein one verse may annul or supersede another. This study aims to analyze both classical and contemporary scholars' perspectives on nāsikh-mansūkh and to propose recommendations for advancing research in the fields of Qur’anic exegesis and uṣūl al-fiqh. Utilizing a qualitative approach and literature analysis, the research provides a nuanced understanding of the divergent views on abrogation and its implications for the interpretation and application of Islamic law in modern contexts. The findings indicate that the concept of nāsikh-mansūkh remains relevant, albeit interpreted differently by classical and contemporary scholars. Classical figures such as Imām al-Shāfiʿī and Jalāl al-Dīn al-Suyūṭī viewed abrogation as a process of legal adjustment in response to evolving societal conditions. In contrast, contemporary scholars like ʿAbd al-Wahhāb Khallāf and Muḥammad Ṭāhā argue that nasikh should not be seen merely as legal cancellation but rather as a flexible legal mechanism that accommodates the changing needs of society. Imām al-Shāfiʿī, a leading authority in uṣūl al-fiqh, emphasized that this concept does not signify contradiction but reflects the flexibility and wisdom inherent in Islamic teachings, enabling legal rulings to adapt to dynamic social realities.